The impact of voluntary environmental agreements on firms' incentives for technology adoption - Markus A. Lehmann (Fondazione Eni Enrico Mattei (FEEM), 2000)
The paper reconsiders the Porter hypothesis in an offer/counter-offer bargaining model, in which a welfare-maximising regulator and an industry representative negotiate over which regulatory instrument to apply with which stringency. The possibility to contest planned regulation in the political arena is given as an outside option of the bargaining model. Policy instruments differ in their impacts on firms' profits and market shares, which yields different incentives for technology adoption. Furthermore, means of direct regulation may lead to an implicit cartelisation of the industry. This latter feature shapes the actors' equilibrium threat position, which, in turn, influences incentives to contest the regulation and the subsequent regulatory outcome. Depending on the parties' respective position in the political contest, the implementation of voluntary agreements or of other (negotiated or mandatory) policy instruments, as well as their impact on the technology adoption incentives, is endogenously derived within this single model.
Keywords: D78; C78; 330; Voluntary agreements; technology adoption; Porter Hypothesis; Selbstverpflichtung; Umweltmanagement; Technologiewahl; Anreizregulierung; Theorie